Prosthetic endocarditis, clinical and surgical insights of lifethreatening situations (2020)
Prosthetic valve endocarditis (PVE) is a low incidence microbial infection complicating surgical valve replacements with a very high rate of early mortality. We present a series of 5 patients who required Redo surgical interventions due to PVE as a complication within the first 3 postoperative months. Initial procedures included aortic valve replacement with valved graft conduit or supra-coronary graft, isolated or combined aortic and mitral valve replacements. The diagnosis was established by transesophageal echocardiogram and computed tomography angiography. Complex surgical procedures under hypothermic femoral access cardio-pulmonary by-pass techniques for prosthetic valvular replacements with homografts, biological or mechanical valves are described. Mortality was 40%.